2020
DOI: 10.12928/ijemi.v1i2.1631
|View full text |Cite
|
Sign up to set email alerts
|

The Principal’s Leadership as the Effort to Build Students’ Character

Abstract: Education is an effort to change behavior as well as building the character of the students. The decisive character of students is the foundation for the realization of national dignity in the future. In the education institution, the principal has the responsibility for making an effort to build the students’ character. This research focused on investigating the principal’s leadership in building students’ character. The research method used is descriptive and verification methods—a quantitative method conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…As a result, the principal's competency as the X1 variable influences the character development of the Y variable pupils. This result was supported by (Dekawati, 2020).…”
Section: The Principal's Competence On Student's Character Developmentsupporting
confidence: 63%
“…As a result, the principal's competency as the X1 variable influences the character development of the Y variable pupils. This result was supported by (Dekawati, 2020).…”
Section: The Principal's Competence On Student's Character Developmentsupporting
confidence: 63%
“…Student-oriented learning is actually the process of forming students' independent attitudes towards each responsibility given to them (Santika, 2020). Independent human resources are one of the indicators needed in the development of a nation's civilization that is strong and able to compete globally with creative and innovative ideas that are raised in learning (Dekawati, 2020;Pradana et al, 2021). If independence is well ingrained in students, parents' worries about the survival of their children will disappear, because children who have strong independence can protect themselves from things forbidden by law and religion and will benefit society (Ritonga, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…The study also confirmed that the principal's leadership would influence the behavior of teachers. The better the leadership quality of the principal, the better the behavior of teachers and other school members (Dekawati, 2020;Kin et al, 2018). In general, the leadership quality of the principal will affect the teachers' performance and will further determine the school's success in achieving learning objectives (O'Shea, 2021;Sammons, 2010).…”
Section: Discussionmentioning
confidence: 99%